Swallowing disorders in patients with obstructive sleep apnea: a critical literature review - Gabriele Ramos de Luccas; Giédre Berretin-Felix (Sleep Science)
Patients with obstructive sleep apnea (OSA) may show signs and symptoms of altered swallowing function since repetitive episodes of OSA may cause hypoxia (decreased oxygen concentration in the blood) and hypercapnia (increased carbon dioxide concentration in the blood), as well as neuromuscular changes in the tissues involved, including the pharynx. This study aims to analyze whether patients with OSA show signs and symptoms of altered swallowing function. A literature search was performed in the PubMed, LILACS, Medline, Scopus, and SciELO databases by using the following search strategy: (“dysphagia”) or (“deglutition disorders”) and (“obstructive sleep apnea”) or (“obstructive sleep apnea syndrome”). The included articles were sorted by authors, year, country, journal of publication, and type of study, as well as analyzed according to the objectives, case series, OSA and swallowing assessment methods, results and conclusions. After applying the inclusion and exclusion criteria, ten articles published in medicine, dentistry and physiology journals between 1999 and 2018 were selected. The analysis of the selected articles showed that the number of participants and group structuring vary according to the study and instrumental and objective exams are used to assess swallowing and sleep in most articles. Also, the results show that groups of patients with OSA can present altered swallowing reflex, altered latency time and inspiratory suppression time, and presence of premature posterior escape, residues, penetration and aspiration. Premature posterior escape was the most frequent sign found. In conclusion, patients with OSA may show signs and symptoms of altered swallowing function.